2018
DOI: 10.1536/ihj.17-639
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Saphenous Vein Coronary Bypass Grafting

Abstract: The enormous majority of previous reports focused on evaluating the safety and efficacy of sequential saphenous vein (SV) coronary bypass grafting; however, no reports to date have revealed concern regarding the impacts of the number of distal anastomoses of sequential SV grafting on graft patency after coronary artery bypass grafting (CABG). This single-center retrospective study aimed to evaluate the impacts of three versus two distal anastomoses per single SV conduit on SV graft patency after off-pump CABG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…16 Many studies have shown that there is no substantial difference between single vein and sequential vein grafts. [17][18][19] There were limitations in this study. The study was a singlecenter study; the sample is small.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…16 Many studies have shown that there is no substantial difference between single vein and sequential vein grafts. [17][18][19] There were limitations in this study. The study was a singlecenter study; the sample is small.…”
Section: Discussionmentioning
confidence: 94%
“…Sequential vein grafts can preserve vein length, and off‐pump bypass grafting can accelerate postoperative recovery and reduce the incidence of postoperative complications 16 . Many studies have shown that there is no substantial difference between single vein and sequential vein grafts 17–19 …”
Section: Discussionmentioning
confidence: 99%
“…Pigs can be used to evaluate TEVG growth and plaque formation in short-term studies, while sheep are more suitable for investigating thrombogenicity, calcification, and long-term patency of the grafts, for the reason that sheep develop a very similar lesion of intimal hyperplasia to those found in failed human access grafts and the ovine coagulation system more closely resembles human coagulation than dogs or pigs (Schleimer et al, 2018). Side-toside suturing is sometimes utilized in sequential bypass which sequentially connects 2 or 3 coronary arteries with just one graft (Ji et al, 2018). They provide the most similar physiology to humans and the most convincing results in TEVG researches.…”
Section: Animal Studiesmentioning
confidence: 99%
“…End-to-side suturing is the most common method utilized in cardiovascular surgery. Side-toside suturing is sometimes utilized in sequential bypass which sequentially connects 2 or 3 coronary arteries with just one graft (Ji et al, 2018). Conversely, end-to-end suturing is not that comparable with clinical surgery.…”
Section: Animal Studiesmentioning
confidence: 99%
“…As technological innovations continue to be developed, CABG has been increasingly performed in off-pump mode, which not only allows for faster patient recovery but also results in fewer postoperative complications [14]. In addition, many studies have shown that there is no substantial difference between single vein and sequential vein grafts [15][16][17]. Previous studies mainly used NT technology in on-pump CABG, and most of the vein grafts were single vein grafts.…”
Section: Introductionmentioning
confidence: 99%